Efektifitas Fermentor Fuzzy Digital Terhadap Kualitas Mutu Biji Kopi - Kusmiah, Nurhaya; Waris, Abdul; Manggabarani, Ishak (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2021)
Coffee is one of the potential plantation commodities in Indonesia. Currently, coffee processing has been a common practice in creating processed coffee with a distinctive aroma and taste through the fermentation process to increase the selling price of coffee in the market. This study aims to test the extent of fermentor designed with the application of digital fuzzy to be able to provide a perfect fermentation process so that it can improve the quality of coffee beans or ground coffee. The method used is a Completely Randomized Design to see whether fermentation using a fermenter can improve the quality of coffee beans. Based on the research conducted, the results obtained that the performance of the fermenter is very good, characterized by no overshoot and offset. Testing the quality of the fermented coffee beans showed that the pulp was easily separated, the color of the beans was darker, it is notated by L* = 31.63, the total acid was about 20%, and the pH of coffee products is 6 which is classified as safe for consumption.